Concurrent Validity of the Defense and Veterans Pain Rating Scale in VA Outpatients. Issue 11 (8th August 2015) - Nassif, Thomas H.; Hull, Amanda; Holliday, Stephanie Brooks; Sullivan, Patrick; Sandbrink, Friedhelm
Abstract: Objective: The purpose of this report is to investigate the concurrent validity of the Defense and Veterans Pain Rating Scale (DVPRS) with other validated self‐report measures in U.S. veterans. Design: This correlational study was conducted using two samples of outpatients at the Washington, DC Veterans Affairs Medical Center who completed self‐report measures relevant to pain conditions, including pain disability, quality of life, and mental health. Study 1 and 2 consisted of n = 204 and n = 13 participants, respectively. Methods: Bivariate Spearman correlations were calculated to examine the correlation among total scores and subscale scores for each scale of interest. Multiple linear regressions were also computed in Study 1. Results: In Study 1, the DVPRS interference scale (DVPRS‐II) was significantly correlated with the Pain Disability Questionnaire (PDQ) (ρ = 0.69, P < 0.001) and the Veterans RAND 36‐item Health Survey physical and mental component scales (ρ = −0.37, P < 0.001; ρ = −0.46, P < 0.001, respectively). When controlling for sex, age, and other self‐report measures, the relationship between the DVPRS‐II and PDQ remained significant. In Study 2, pain interference on the DVPRS and Brief Pain Inventory were highly correlated (ρ = 0.90, P < 0.001); however, the intensity scale of each measure was also highly associated with the interference summary scores. Conclusions: These findings provide preliminary evidence for the concurrent validity of the DVPRS as a brief, multidimensional measure of pain interference that make it a practical tool for use in primary care settings to assess the impact of pain on daily functioning and monitor chronic pain over time.